Learning In the Form Of Practice Applications Through Science Subjects In Elementary Schools In East Timor City The City Of Gorontalo - Dr. Yurni Rahman, S.Pd, M.Pd; Yulanti S. Mooduto, M.Pd (Jurnal KomtekInfo, 2020)
Learning in the form of practical applications is a form of real learning activities where students will receive teaching materials at the same time be able to directly prove it through direct practice at school. The long-term objective of the research is that students will be exposed to data interpretation in which they are asked to apply their theoretical knowledge to numbers and use their reasoning skills to make inferences based on the logic and trends of the given data set and can also contribute to the development of education in Indonesia. especially in the city of Gorontalo. Learning in the form of practical applications can be an intermediary for teachers and elementary school students to be able to develop students 'and teachers' way of thinking so as to produce professional teachers and genius students. Currently, the learning conditions are not optimal in achieving the learning objectives, therefore it is necessary to conduct research on learning in the form of practical applications with this research to answer the causes of the less than optimal implementation of the effective learning process in Gorontalo City and efforts to increase teacher professionalism can be realized. This research uses qualitative research. The type of research is program evaluation using the explanatory model. The main data collection techniques are interviews, observation and documentation of various data sources (informants) that are directly related to, Augmented Reality, Virtual Reality, or the Internet of Things. This research is not only directed at the results (product). However, the other three components are also evaluated, because the four components are very closely related. Apart from interviews, data collection was also carried out using observation and documentation techniques. The observation technique was carried out on the learning process and product (result) in the form of practical application in Gorontalo City, while the documentation technique was carried out on documents relating to the process and product (result). In this aspect, the highest percentage (%) is that students spend about 1 hour / day at 28%, while the lowest is that students spend 4-5 hours / day or 11.6%. From this percentage, it can be concluded that the percentage of students who spend or spend time reading science subjects is still low so that the efforts of teachers and parents and the surrounding environment are needed so that students' interest in reading is maximized.